A Study Of Performance Appraisal Acceptane And Employees' Performance In Multinational Companies In Malaysia - Amat Taap Manshor (2002)
The objectives of this study were to 1) develop valid measures of participation, goal setting, feedback, information quality, information validity, link performance with personnel decisions and fairness; 2) to develop valid and reliable measures of performance appraisal (PA) effectiveness scale, PA acceptance scale, and individual productivity scale; 3) to gauge the impact of participation , goal seeting, feedback, information quality , information validity, link performance with personnel decisions and fairness with performance appraisal acceptance and effectiveness, and employees' performance; 4) to identify the impact of demographic variables of respondents, performance appraisal characteristics and country of origin on performance appraisal acceptance and effectiveness and employees' performance.